A Hundred Year Old Agony And Its Reflections: Wilfred Owen`s Anthem for Doomed Youth - Metin Timuçin (Skad)
As agreed by majority of literary critics with regard to English Literature, one of the most outstanding aspects of World War I is the amount of excellent poetry it inspired. What is perhaps the greatest body of war poetry ever written was produced by British poets from 1914 to 1918. Indeed, as emphasized by Roby (1993), those few bloody years spawned into “two generations” ofwar poets; the first caught up in the awful and blind patriotism of the hour, among them are Rupert Broke, Julien Grenfel, Robert Nichols and the second composed of anti-war satirists and soldier-poets of English Literature; Siegfried Sassoon and Wilfred Owen. This paper will focus on a poem of one of soldier-poets, Wilfred Owen`s Anthem for Doomed Youth. The main aim ofthe paper will be to dwell on different poetic strategies used by the poet via stylistic analysis, and an attempt will be made to illustrate how stylistic features of the poem contribute to the overall meaning of the poem.